The Urgency Of The Youth Red Cross Extracurricular Activity Program In Shaping Students Ta'awun Behavior At SMK Negeri 1 Bengalon - Fattul Jannah, Siti Sri; Faelasup; Mubaidilla, Miftakhul Rizal (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
The purpose of this study was to determine the urgency of the youth red cross extracurricular activity program in shaping students ta'awun behavior at SMK Negeri 1 Bengalon. Meanwhile, the type of research that the author uses in this research is field research using a qualitative research approach. In collecting data, the author uses data collection techniques, namely participant observation, structured interviews, documentation. Based on the results of the study, it can be concluded that the ta'awun behavior of students at SMK Negeri 1 Bengalon can be applied by some students by forming ta'awun behavior such as providing medical assistance to those in need. The PMR extracurricular activity program at SMK Negeri 1 Bengalon is like developing the character of volunteerism. The urgency of the youth red cross extracurricular activity program in shaping students' ta'awun behavior is that it can build ta'awun character and instill humanitarian values.